Choice, agency consent and coercion: Complex issues in the lives of prostituted and trafficked women. (May 2017) - O'Connor, Monica
Abstract: This article examines the complexity of the concepts of choice, agency and consent in women and girls' entry into and experience within the commercial sex trade. Interpretative Phenomenological Analysis is used to analyse a series of in-depth interviews with prostituted and trafficked women in Ireland. The interviews reveal the circumscribed nature of individual choice and agency and the coercive context in which sexual consent is obtained within the power structure of the prostitution contract. The narrative accounts reveal the trauma of rape and sexual assault, but also the profoundly harmful consequences for women of acquiescing to multiple unwanted and degrading sexual acts for payment. This study also enhances our understanding that women's lived experience does not reflect a rigid demarcation between those who were coerced or trafficked, and those who are perceived to have exercised choice in their entry into prostitution. Highlights: Consent not defining factor in sexual acts being unwanted or harmful in prostitution Choice and agency meaningless if not contextualised in discourse on prostitution Critical need to differentiate adult consensual sex from prostitution sex Challenges the silence on the harm of unwanted sex acts in sex work literature